2022
DOI: 10.1186/s12877-022-03662-8
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the quality of life of long-term care service users in Japan: a cross-sectional questionnaire study

Abstract: Background In Japan’s super-aging society, the number of long-term care service providers is increasing, and the quality of care is a matter of concern. One aspect of the quality of care is the user’s quality of life. The questionnaires EQ-5D and WHO-5 are representative indicators of quality of life. Herein, we aimed to measure the quality of life in long-term care service users in Japan and to clarify the relationship between quality of life and the level of care required. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…With regard to sensitivity to known-group differences we found that both EQ-5D indices and EQ VAS discriminate well between different needs of care, i.e. care levels, which is in line with findings from Hara and colleagues [ 38 ] for the Japanese version of the 5L. Similarly, we observed satisfactory ability to differentiate different levels of general health status, which was also confirmed based on the 3L index for older adults in the literature [ 39 , 40 ].…”
Section: Discussionsupporting
confidence: 91%
“…With regard to sensitivity to known-group differences we found that both EQ-5D indices and EQ VAS discriminate well between different needs of care, i.e. care levels, which is in line with findings from Hara and colleagues [ 38 ] for the Japanese version of the 5L. Similarly, we observed satisfactory ability to differentiate different levels of general health status, which was also confirmed based on the 3L index for older adults in the literature [ 39 , 40 ].…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, having caregivers in close proximity seems to be one of the benefits of being in the nursing home [22]. Hara et al (2022) researched the quality of life among Japan residents of nursing homes and found out that it was definitely worse than that of the general older population. Moreover, it tended to be especially low among males and those suffering specific diseases being under 65 years old.…”
Section: Discussionmentioning
confidence: 99%
“…It also gradually decreased with the increasing level of dependency (care required for everyday existence). The scholars indicated that the measurement of the quality of life of nursing homes' residents is essential for taking steps to improve and manage it [23].…”
Section: Discussionmentioning
confidence: 99%